The sociology student writer's manual - .; Rettig, Richard P.; Scott, Gregory M.; Johnson, William A. (Prentice Hall, 1999)
This book is divided into five parts: A Handbook of style for sociology; How to conduct research in sociology; Thinking critically and arguing persuasively; Critical thinking exercises for introductory courses; and Sociology papers for advanced courses.